Public Sector Reforms in Africa: What Lessons have we Learnt? - Kagambirwe Karyeija, Gerald (In Forum for Development Studies, 2012)
Several public sector reforms (PSR) have taken place in Africa over the last few decades with varying degrees of success; these range from very excellent performance, to limited success and then failure. However, regardless of the evaluation results, they have without a doubt had an impact on the way we understand and shape public management on the African continent. Inevitably, a number of insights and lessons have been gained on the subject matter. In this article, I suggest that a number of lessons have been learnt which should guide reformers to improve on public sector reforms and scholars to seek further explanations for failure and success. There is also the need for students of public sector reforms to question further the prevailing assumptions and theories underpinning these reforms. The 10 lessons highlighted are: (1) there is need to acknowledge the importance of culture and context, because at times local values contradict the content of reform efforts; (2) PSR need both political support and support from the civil society; (3) PSR take time to bear fruit; (4) incremental implementation may be better; (5) not all support for PSR is altruistic; (6) corruption still hinders reform in Africa; (7) there is a need to revisit the role of donors; (8) first things first – let us create a credible public sector before we reform it; (9) ownership of reform programmes by African governments and other stakeholders is necessary; and (10) despite these reforms, Africa still remains poor.
Keywords: Public sector reforms; Africa; New public management; Civil service; Donors